Psychopathic Traits in Childhood and Depression Symptoms in Adolescence: the Mediating Role of Peer Victimization - Fontaine, Nathalie M. G. (Journal of developmental and life-course criminology, 2024)
Youth with psychopathic traits are at risk of engaging in physical aggression and being exposed to victimization from peers, which, in turn, is associated with symptoms of depression. The mechanisms underlying the associations between psychopathic traits, peer victimization, and subsequent depression symptoms remain unclear. Using data from the Quebec Longitudinal Study of Child Development (n = 2,120 youth; 49.1% female) and path analyses, we tested whether peer victimization (at 10–12 years) mediated the associations between psychopathic traits in childhood (at 6–8 years) and depression symptoms in adolescence (at 15–17 years). We also examined if the association between psychopathic traits and peer victimization was moderated by child sex, anxiety symptoms, and physical aggression. Teachers assessed psychopathic traits and peer victimization in childhood. Participants reported on their depression symptoms in adolescence. Findings showed that the association between childhood psychopathic traits and depression symptoms in adolescence was mainly indirect and (partly) operated via peer victimization. This indirect association appeared to be particularly salient for children who manifested low levels of physical aggression. The association between psychopathic traits and later depression symptoms via peer victimization could be less typical of children with high levels of physical aggression. This study highlights the importance of the mediating role of peer victimization and the moderating role of physical aggression when examining the association between psychopathic traits and subsequent depression symptoms.